2011
DOI: 10.1016/j.ntt.2010.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Discriminative stimulus effects of cocaine and amphetamine in rats following developmental exposure to polychlorinated biphenyls (PCBs)

Abstract: Polychlorinated biphenyls (PCBs) are environmental neurotoxicants known to affect the brain dopaminergic (DA) system. This project investigated whether developmental exposure to PCBs would alter the discriminative stimulus effects of psychostimulant drugs known to act on the DA system. Female Long-Evans rats were orally exposed to 0, 3, or 6 mg/kg/day of an environmentally relevant PCB mixture from four weeks prior to breeding through weaning of their litters on PND 21. When they reached adulthood one male and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 58 publications
3
18
0
Order By: Relevance
“…These findings are in line with our expectations and replicate previous research using the same dosing regimen with the Fox River PCB mixture (Sable et al, 2009; 2010)…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These findings are in line with our expectations and replicate previous research using the same dosing regimen with the Fox River PCB mixture (Sable et al, 2009; 2010)…”
Section: Discussionsupporting
confidence: 93%
“…Dosing procedures, including a rationale for the doses selected have previously been explained in detail (Kostyniak et al, 2005; Sable et al 2006; 2009; 2010). Briefly, a stock solution of the Fox River PCB mixture (Kostyniak et al, 2005) was diluted with corn oil to make three dosing solutions: 0 μl/ml PCBs (corn oil only), 7.5 μl/ml PCBs, and 15.0 μl/ml PCBs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously mentioned, differences in cocaine (unpublished results) and amphetamine (Poon et al, 2013) behavioral sensitization and drug discrimination (Sable et al, 2011) have been found in adult rats perinatally exposed to PCBs in comparison to controls. Likewise, other studies using animal models have reported that developmental exposure to lead (Clifford et al, 2011; D.…”
Section: Discussionmentioning
confidence: 64%
“…First, alterations in the discriminative stimulus effects of cocaine and amphetamine were observed in adult rats perinatally exposed to PCBs (Sable, Monaikul, Poon, Eubig, & Schantz, 2011). Also, research demonstrated that the locomotor activating effects following a single intraperitoneal amphetamine injection, as well as behavioral sensitization to repeated intraperitoneal injections of amphetamine, were affected by perinatal PCB exposure (Poon, Monaikul, Kostyniak, Chi, Schantz, & Sable, 2013).…”
Section: Introductionmentioning
confidence: 99%